2014
DOI: 10.4236/ajps.2014.526420
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expression Profiling of a CONSTANS-Like Gene and Two FLOWERING LOCUS T-Like Genes from Spinacia oleracea L.

Abstract: Spinach (Spinacia oleracea L.) develops leaf rosettes under short-day conditions, and starts reproductive growth including bolting and flowering under long-day conditions. Japanese people prefer Oriental spinach that bolts easily with a shorter photoperiod than European spinach. This is one of the main reasons that Oriental spinach is difficult to grow year-round. In order to understand spinach flowering mechanisms and obtain knowledge for spinach breeding, we isolated one CONSTANS-like (COL) and two FLOWERING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Therefore, floral transition is guaranteed [ 87 , 88 ]. Interestingly, several studies have revealed that DELLA regulates hypocotyl elongation by interacting with PIFs [ 75 ], contributing to floral transition by interacting with SPL [ 7 ], FD [ 10 ] and SOC1 [ 24 , 62 ]. SOC 1 plays an important role in regulating floral transition by integrating signals involved in all pathways, as well as interacting with many other genes to regulate floral transition [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, floral transition is guaranteed [ 87 , 88 ]. Interestingly, several studies have revealed that DELLA regulates hypocotyl elongation by interacting with PIFs [ 75 ], contributing to floral transition by interacting with SPL [ 7 ], FD [ 10 ] and SOC1 [ 24 , 62 ]. SOC 1 plays an important role in regulating floral transition by integrating signals involved in all pathways, as well as interacting with many other genes to regulate floral transition [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Great progress has been made in understanding the factors that trigger floral transition [ 4 ]. A set of floral transition-related genes, such as SPL ( Squamosa-promoter binding protein-like ) [ 5 7 ], TOC ( Timing of cab expression 1 ) [ 8 ], LUX ( Luxarrhythmo ) [ 8 ], PIF ( Phytochrome interacting factor ) [ 9 ], CO ( constans ) [ 10 ], FRI ( Frigida ) [ 11 ], GA20ox ( GA20oxidases ) [ 7 ], GA3ox ( GA3oxidases ) [ 12 ], SOC1 ( Suppressor of overexpression of constans 1 ) [ 13 ], have been detected, in addition to others [ 14 , 15 ]. These genes are mainly categorized into five major pathways that regulate floral transition, including the age pathway, photoperiod and circadian clock pathway, autonomous pathway, vernalisation pathway and GA pathway [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is typically consumed as a fresh, cooked or canned vegetable ( Morelock and Correll, 2008 ; Ma et al, 2016 ). The reproductive process usually begins with bolting (the elongation of the stem) ( Mutasa-Göttgens et al, 2010 ), which leads to decreased yields and low quality ( Abe et al, 2014 ). Spinach is easily influenced by the photoperiod ( Chun et al, 2000b ), and bolts in spring ( Tang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The onset and development of the reproductive phase involve the distinct and sequential processes of bolting followed by flowering Mutasa-Göttgens, et al [7]. After transition to the reproductive stage with flowering and bolting, spinach loses its value as an agricultural product, becoming bitter and hard Abe, et al [8]. Bolting is an important agronomy trait to consider in relation to developing spinach cultivars for year-round production, because of its sensitivity to photoperiod Chun, et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Regulations of spinach flowering and bolting by photoperiod and gibberellin have been reported Zeevaart, et al [20,26]; Lee & Zeevaart, 2002, Lee, et al [27,28]. To understand spinach floweringand bolting mechanisms at a genetic level, one CONSTANS-like (COL) and two FLOWERING LOCUS T (FT) homologs were isolated and characterized, which are known to be key factor of the flowering pathway in many plants Abe, et al[8]. Detecting the mechanisms to regulate pathways in control of spinach bolting could promote the related genetic discovering.…”
mentioning
confidence: 99%